Optimal motion of triangular magnetocapillary swimmers - Sukhov, Alexander; Ziegler, Sebastian; Xie, Qingguang; Trosman, Oleg; Pande, Jayant; Grosjean, Galien; Hubert, Maxime; Vandewalle, Nicolas; Smith, Ana-Suncana; Harting, Jens (Journal of Chemical Physics, 2019)
A system of ferromagnetic particles trapped at a liquid-liquid interface and subjected to a set of magnetic fields (magnetocapillary swimmers) is studied numerically using a hybrid method combining the pseudopotential lattice Boltzmann method and the discrete element method. After investigating the equilibrium properties of a single, two, and three particles at the interface, we demonstrate a controlled motion of the swimmer formed by three particles. It shows a sharp dependence of the average center-of-mass speed on the frequency of the time-dependent external magnetic field. Inspired by experiments on magnetocapillary microswimmers, we interpret the obtained maxima of the swimmer speed by the optimal frequency centered around the characteristic relaxation time of a spherical particle. It is also shown that the frequency corresponding to the maximum speed grows and the maximum average speed decreases with increasing interparticle distances at moderate swimmer sizes. The findings of our lattice Boltzmann simulations are supported by bead-spring model calculations.
CRIS-Team Scopus Importer:2019-10-08

Regimes of motion of magnetocapillary swimmers - Sukhov, Alexander; Hubert, Maxime; Grosjean, Galien; Trosman, Oleg; Ziegler, Sebastian; Collard, Ylona; Vandewalle, Nicolas; Smith, Ana-Suncana; Harting, Jens (European Physical Journal E, 2021)
The dynamics of a triangular magnetocapillary swimmer is studied using the lattice Boltzmann method. We extend on our previous work, which deals with the self-assembly and a specific type of the swimmer motion characterized by the swimmer's maximum velocity centred around the particle's inverse viscous time. Here, we identify additional regimes of motion. First, modifying the ratio of surface tension and magnetic forces allows to study the swimmer propagation in the regime of significantly lower frequencies mainly defined by the strength of the magnetocapillary potential. Second, introducing a constant magnetic contribution in each of the particles in addition to their magnetic moment induced by external fields leads to another regime characterized by strong in-plane swimmer reorientations that resemble experimental observations.
CRIS-Team WoS Importer:2021-05-14

Scallop Theorem and Swimming at the Mesoscale - Hubert, Maxime; Trosman, Oleg; Collard, Ylona; Sukhov, Alexander; Harting, Jens; Vandewalle, N.; Smith, Ana-Suncana (Physical Review Letters, 2021)
By comparing theoretical modeling, simulations, and experiments, we show that there exists a swimming regime at low Reynolds numbers solely driven by the inertia of the swimmer itself. This is demonstrated by considering a dumbbell with an asymmetry in coasting time in its two spheres. Despite deforming in a reciprocal fashion, the dumbbell swims by generating a nonreciprocal Stokesian flow, which arises from the asymmetry in coasting times. This asymmetry acts as a second degree of freedom, which allows the scallop theorem to be fulfilled at the mesoscopic scale.
CRIS-Team WoS Importer:2021-06-25